Water Quality Relationship with FCR Value in Intensive Shrimp Culture of Vannamei (Litopenaeus vannamei) - Heri Ariadi; Abdul Wafi; Supriatna (Samakia : Jurnal Ilmu Perikanan, 2020)
FCR or feed conversion ratio is one of the strategic indicators on pond production which is very important for determining the costs incurred during the shrimp culture period. The purpose of this study was to examine the relationship between water physico-chemical parameters and the conversion rate of shrimp feed in intensive shrimp ponds (Litopenaeus vannamei). The research method used in this study is the ex-pose facto design during shrimp culture cycle with uniformity of treatment during the cultivation process, then the research collective data obtained periodically is analyzed by multiple linear regression. The results of this study indicate that all pond water quality variables based on quality standards are still in accordance with the standards intended for aquaculture. While based on regression analysis and t-test, the temperature variable is the only parameter that has a direct influence on the FCR efficiency by shrimp. As well as temperature, salinity, and alkalinity variables are parameters that have a close level of relationship to the FCR value in the ponds of 84.1%, 79.1%, and 69.9%. The conclusion of this study is that in intensive ponds the parameters of temperature, salinity, and alkalinity are water quality parameters that have a close relationship with the efficiency of FCR values ​​in ponds, with temperature parameters being the water quality variable which has a direct influence on the effectiveness of the feed conversion ratio by shrimp.